Extraction of Zingiber Zerumbet (L) Smith oil by using soxhlet extraction method - Wahida, Amat Fadzil (2010)
In this research, the soxhlet extraction method was used to extract oil from Zingiber Zerumbet (L) Smith rhizomes. The main chemical component in the oil which is zerumbone, has the potential as anticancer, anti-HIV and anti-inflammatory. The examined parameters were investigated are the effect of solvent and extraction time on extraction yield. The solvent used were dichloromethane, benzene and methanol. The extraction time was varied for 4 hr, 6 hr, 8 hr and 10 hr. Then the oil extracts obtained were evaporated using rotary evaporator to get concentrated oil. Then, the extracted oil was analyzed using GCMS to determine the oil composition. GCMS analysis result shows that extracted oil contain zerumbone and α-caryophyllene. Extraction using methanol produced higher yield compared to another solvent. The best extraction time is 6 hours extraction.